2017
DOI: 10.1016/j.ijsu.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effect of intravertebral vacuum cleft with osteoporotic vertebral compression fractures: A systematic review and meta-analysis

Abstract: The IVCs had an important effect of therapeutic efficacy in PVA for the treatment OVCFs. Therefore, we strongly recommend its strict observation and follow-up for the IVCs patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 18 publications
6
32
0
1
Order By: Relevance
“…So Kümmell's disease is also referred to as delayed post-traumatic vertebral collapse disease, nonunion of vertebral fractures, and vertebral ischemic necrosis [1,2,17]. Previous studies have suggested that IVC is mainly located in the thoracolumbar region [4,18], which is similar to the segmental distribution of the two groups of patients in this study. 87.5% of the fractured vertebral bodies were located in the thoracolumbar segment, most of which were wedge fractures.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…So Kümmell's disease is also referred to as delayed post-traumatic vertebral collapse disease, nonunion of vertebral fractures, and vertebral ischemic necrosis [1,2,17]. Previous studies have suggested that IVC is mainly located in the thoracolumbar region [4,18], which is similar to the segmental distribution of the two groups of patients in this study. 87.5% of the fractured vertebral bodies were located in the thoracolumbar segment, most of which were wedge fractures.…”
Section: Discussionsupporting
confidence: 72%
“…examination can discover the late-onset collapse of vertebrae and characteristic change of intravertebral vacuum cleft (IVC), which is considered the one of important inducing factors of injured vertebral progress after the collapse, deformity of kyphosis, intractable back pain and spinal cord damage after OVCF [4].…”
mentioning
confidence: 99%
“…the IVC refers to a significant radiolucency (gas containing), which is located centrally or adjacent to the vertebral body endplates as seen on CT or plain radiographs. On MRI, it is usually shown as a low signal intensity on a T1-weighted image and as a high signal or a low signal on a T2weighted image, depending on whether the fluid or gas fills the cleft [4]; ④ Dual energy X-ray measurement of bone mineral density (BMD) T value was less than − 2.5; ⑤ PVP or PKP was conducted with bilateral pedicle; ⑥ Follow-up time was more than 2 years; ⑦ Postoperative calcium supplementation and anti-osteoporotic drugs were applied; ⑧ No fall or other trauma occurred. Exclusion criteria are as follows: ① Patients with severe cardiopulmonary dysfunction; ② Patients with coagulopathy; ③ Patients with local or systemic infection; ④ Patients with nerve root or spinal cord compression symptoms; ⑤ Patients with pathological fractures other than osteoporosis.…”
Section: Selection Criteriamentioning
confidence: 99%
“…Kümmell's disease is also known as nonunion after OVCF, delayed vertebral osteonecrosis after trauma, and delayed vertebral collapse [2,3]. Imaging examination can discover the late-onset collapse of vertebrae and characteristic change of intravertebral vacuum cleft (IVC), which is considered one of important inducing factors for injured vertebral progress after the collapse, deformity of kyphosis, intractable back pain and spinal cord damage after OVCF [4].…”
Section: Introductionmentioning
confidence: 99%
“…PVP surgery can reduce the risk of vertebral wedge change and nerve injury in Kümmell's disease, so early PVP surgery should be performed [7]. However, between OVCFs and Kümmell's disease, the clinical e cacy, clinical characteristics, and complications of PVP treatment are still uncertain [8].…”
Section: Introductionmentioning
confidence: 99%